Psychoanalysis and theology: Jacques Lacan and Paul - Hackett, Charles D. (Journal of religion and health, 1982)
The nature of humanityor the human situation-has been an area of thought intensely studied by theologians and philosophers for centuries. In more recent times, however, psychology has made serious advances into this field of inquiry. It has been able to provide insights applicable to previous theological ideas. The author brings to the reader's attention his twofold purpose: to present an interpretation of the human situation as understood by Jacques Lacanas informed by such forerunners as Sigmund Freud and Martin Heidegger and expressed by psychoanalytic method. These same ideas are then examined in light of the writings of St. Paul. From a sensitive study of these two thinkers the author has been able to draw numerous correlations pertinent to contemporary studies within religion and psychology.